Frontispiece: A Rapid and Sensitive Strip‐Based Quick Test for Nerve Agents Tabun, Sarin, and Soman Using BODIPY‐Modified Silica Materials. Issue 32 (27th July 2016) - Climent, Estela; Biyikal, Mustafa; Gawlitza, Kornelia; Dropa, Tomáš; Urban, Martin; Costero, Ana M.; Martínez‐Máñez, Ramón; Rurack, Knut
Abstract : Rapid Test for Nerve Gases Covalent anchoring of a fluorescent BODIPY indicator into the channels of mesoporous SBA silica microparticles yielded a sensor material that selectively detects traces of chemical warfare agents through an intramolecular cyclization reaction leading to a non‐fluorescent product. When the hybrid particles are sterically immobilized on test strips, a rapid and simple alarm system is obtained that can in future be used on suits of first responders as visualized here by Marco Dinter. More information can be found in the Communication by K. Rurack et al. onpage 11138 ff.